(untitled) (Research, Society and Development, 2022)
Consumers re increasing demand for foods with healthier and more functional attractions. The addition of hibiscus flour in the dough formulation can improve the color, flavor and functional properties of cookies. Within this context, the present study aimed to evaluate the physical and chemical parameters (moisture, crude protein, fat, dietary fiber, minerals, carbohydrates, energy value, water activity, pH and color) of hibiscus flour, beetroot flour and cookies containing hibiscus flour instead of wheat flour. For this, two cookies were formulated, with 0% and 50% inclusion of hibiscus flour (FH) in place of wheat flour (FT). The results showed that the inclusion of 50% of hibiscus flour (FH) provided a cookie with a higher fat (7.31%), fiber (6.11%) and minerals (3.59%) content. lower values ​​in stability parameters (pH = 3.56 and Aw = 0.59). In the color attribute, a cookie with a color closer to red (°Hue = 0.75). It is concluded that the inclusion of 50% of FH in the cookie formulation resulted in a high fiber cookie that could be classified as a functional food. The pH and Aw obtained guarantee an increase in the shelf life of the product as it is a barrier to microorganisms.